PSYCHOLOGICAL FACTORS OF STRESS RESISTANCE OF SOCIOECONOMIC PROFILE SPECIALISTS (Psychology Travelogs, 2023)
The article provides the theoretical analysis of the stress resistance of socionomic specialists in the scientific psychological literature. Here are outlined the methodological approaches to determining the essence of stress resistance. Theoretical and methodological understanding of the scientific literature allowed to determine stress resistance the essence of as a psychological phenomenon which is characterized by a high level resistance to stress and a high level of reflection. It was determined that stress resistance a important component of a specialist's mental health. The article reveals the definitions: stress, professional stress, stress resistance, emotional stability, psychological stability, mental health, stress factors,psychological factors of stress resistance. The focuses on the influence of the psychological factors contribute to development of stress resistance of a socio-economic specialist. It was determined psychological factors of stress resistance and the psychological barriers stress resistance of  specialists in the socio-economic the profile.In the article, the stress resistance is understood as the complex of the personal professional qualities, which assist in professional tasks solving in the psychological sphere. The stress resistance characterized by a high level adaptation, a high level work capacity and a high level of mental health.The results of an empirical study of the level of stress resistance by appropriate to the methods. According to the results of the study, it was determined that the average level of stress resistance among specialists of the socionomic profile. We see the prospect of further research in the implementation and development psychological support for the development of stress resistance of socio-economicspecialists.
Keywords: stress; professional stress; stress resistance; emotional stability; psychological stability; mental health; stress factors; psychological factors of stress resistance